Effect of mycorrhizal soil and green manures on growth of Ipil Ipil (Leucaena diversifolia L.) - Bhattarai, Nabin; Vaidya, Geeta Shrestha; Baral, Bikash (Scientific World, 2012)
A pot trial research work of powder of Lantana camara L., Eupatorium adenophorum Spreng. and mycorrhizal soil on growth of Ipil Ipil (Leucaena diversifolia L.) fodder plant was conducted. Fifty gram of each green manure in powder form and mycorrhizal soil were used in each pot. Including control, altogether four treatments were made and each has fifty replicates. The treatment with green manure from Lantana camara showed maximum growth, survival and germination of the plants with maximum average length of 21.25 cm and 37.96 cm respectively, followed by Eupatorium adenophorum (16.51 cm and 23.46 cm) which was statistically significant (P < 0.05). Survival of plants was higher Lantana camara. Number of mycorrhizal spores, soil bulk density and water holding capacity was higher in Lantana treated soil followed by Eupatorium adenophorum, Mycorrhizal soil and control. The nutrient status of the soil improved than the eroded soil. The soil sample treated with Eupatorium adenophorum showed the maximum percentage of organic matter, potash, phosphorus and nitrogen content i.e. 1.95, 58.14, 13.65, 0.17, respectively followed by Lantana, mycorrhiza and control. The green manures prepared from these plants and mycorrhizal soil can be used for the growth of plants which improves the nutrient status of soil and increases the mycorrhizal biomass stabilizing the eroded and land slided area. Scientific World, Vol. 10, No. 10, July 2012 p66-69 DOI: http://dx.doi.org/10.3126/sw.v10i10.6864